ANALYSIS OF ECONOMIC EMPOWERMENT OF ORNAMENTAL PLANTS FARMERS IN BONDOWOSO DISTRICT - Eko Raharto; Izzah Dienillah (International Conference on Humanity Education and Society (ICHES), 2022)
ABSTRACTThe Bondowoso Ornamental Plant Farmers Association (APTHB) was the focus of this research. The purpose of the research was to determine the Association’s model of economic empowerment for this members, as well as the members income and welfare before and after participation in the empowerment program. To obtain data, information, and documentation, descriptive qualitative analysis was used, and that included interview and observation techniques. The results showed that the model of the Associations empowerment program was successful in increasing the number of ornamental plant production and marketing though offline and online media, resulting in a direct impact on farmer’s income and welfare the empowerment program includes stages including such member recruitment, monitoring business development, cultivation training and business management, and offline marketing media (flower market, car free day, and ornamental plant outlets at supermarket) as well as online media (live sale Instagram) by coming directly to farmers gardens. The Associations empowerment program has had a positive impact, having farmers achieving increased cultivation competence, business management, increased income, and increased family welfare.Keywords: Empowerment, Income, Welfare, Ornamental Plant Farmers.